A Study of Landslide Areas Mitigation and Adaptation in Palupuah Subdistrict, Agam Regency, West Sumatra Province, Indonesia - Oktorie, Olivia (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to determine the alternative policies of landslide area mitigation and adaptation in Palupuah Subdistrict, Agam Regency, West Sumatra Province, Indonesia. This research was descriptive research using mixed method. The data collection used purposive sampling by adapting the sample to criteria. The samples were Palupuah Subdistrict government agencies (the Department of Social, the Head of Palupuah Subdistrict, National Disaster Management Agency), the experts, and the society leaders of Palupuah Subdistrict. The results and discussion of the alternative policies of landslide area mitigation in Palupuah Subdistrict, Agam Regency, West Sumatra Province, Indonesia are: (1) conducting the settlements management in areas with landslides risk of the greatest weight rated (0,795), (2) strengthening the slope vegetatively (0.792), (3) strengthening the slope mechanically (0.769), and (4) developing land allotment landslides based (0.750). The alternative policies of landslide area adaptation in Palupuah Subdistrict, Agam Regency, West Sumatra Province, Indonesia are: (1) avoiding building houses in the steep slopes area, (2) performing the agricultural pattern landslide mitigation based, (3) creating the sewerage in the ​​water cycle area, and (4) making the rules based on the local wisdoms that respond to the landslide.